Pengembangan Flipbook Modul Berbasis Engineering Design Process (EDP) untuk meningkatkan Literasi Sains Siswa SMP dalam Pembelajaran IPA - Mustofa Mustofa; Pramudya Dwi Arista Putra; Zainur Radyid Ridlo (UIN Sultan Aji Muhammad Idris Samarinda, 2023)
Scientific literacy is one of the right keys to fight the challenges of the 21st century, this is because scientific literacy can be useful for overcoming problems in the surrounding environment by producing useful products. The purpose of this study is to examine the validity, practicality and effectiveness of module flipbooks based on the engineering design process (EDP). The type and design of the research includes the type of research (research and development) R & D that has been developed using the Plomp research design through the following steps, namely preliminary research, prototyping stage, and assessment phase. Data collection uses several techniques, namely questionnaires, scientific literacy tests and interviews. The instruments in this are validation sheets, student response questionnaire sheets, and observation sheets. Whether or not the module is appropriate is measured using a validation sheet, while the student response anchor sheet is used to measure students' interest in the product that has been developed. The results of the validity analysis of 90% obtained from the three validators means it is very valid, practicality is 94% which means it is very practical with practical indicators in the form of students' fluency in using the flipbook module, and an effectiveness of 0.68 gain from n-gain analysis which means it is quite effective as well as the results of the student response questionnaire sheet in the good category by 72%. The results of the analysis obtained show that using the EDP-based module flipbook where the EDP steps contained in the module flipbook are valid, practical, and effective in learning science can improve scientific literacy of junior high school students.